Light-Stress Response Mediated by the Transcription Factor KlMga2 in the Yeast Kluyveromyces lactis - Camponeschi, Ilaria; Montanari, Arianna; Beccaccioli, Marzia; Reverberi, Massimo; Mazzoni, Cristina; Bianchi, Michele M. (Frontiers in Microbiology, 2021)
In unicellular organisms like yeasts, that do not have specialized tissues for protection against environmental challenges, the presence of cellular mechanisms to respond and adapt to stress conditions is fundamental. In this work, we aimed to investigate the response to environmental light in Kluyveromyces lactis. Yeast lacks specialized light-sensing proteins; however, Saccharomyces cerevisiae has been reported to respond to light by increasing hydrogen peroxide level and triggering nuclear translocation of Msn2. This is a stress-sensitive transcription factor also present in K. lactis. To investigate light response in this yeast, we analysed the different phenotypes generated by the deletion of the hypoxia responsive and lipid biosynthesis transcription factor KlMga2. Alterations in growth rate, mitochondrial functioning, ROS metabolism and fatty acid biosynthesis, provide evidence that light was a source of stress in K. lactis and that KlMga2 had a role in the light-stress response. The involvement of KlMsn2 and KlCrz1 in light stress was also explored.